Analysis of Digital Bank Services in Indonesia Based on Consumer Perception - Khairina Natsir; Agus Zainul Arifin; Claudius Barly Sadhewa; Della Aprilia; Selvi Dharsono (International Journal of Application on Economics and Business, 2023)
This study aims to find out that Financial Performance in a company that provides Digital Bank services can be influenced by consumer perceptions represented through the variables of Customer Experience, Customer Satisfaction and Customer Loyalty. The data were collected using a survey aimed at users of Digital Bank services in Indonesia which was then tested statistically by analysis of the Outer Model and the Inner Model using Partial Least Square (PLS). Unlike other studies, this study used NPS (Net Promoter Score) as an indicator of Financial Performance Customer Experience, Customer Satisfaction and Customer Loyalty. The results of the study showed that Customer Experience, Customer Loyalty and Customer Satisfaction had a positive effect on Financial Performance, Customer Experience had a positive effect on Customer Loyalty and Customer Satisfaction. This study also found that Customer Loyalty and Customer Satisfaction mediate the influence of Financial Experience on Financial Performance.